Pengaruh Content Marketing, Online Customer Review, dan Harga terhadap Keputusan Pembelian Produk Skincare Hanasui melalui Aplikasi Tiktok - Siti Mutmainnah; Pemilia Sulistyowati (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to understand and analyze the impact of content marketing on purchasing decisions for Hanasui skincare products through the TikTok application, to understand and analyze the long-term impact of online customer reviews on purchasing decisions for Hanasui skincare products through the TikTok application, to understand and analyze the long-term impact of prices on purchasing decisions for Hanasui skincare products through the TikTok application, and to understand and analyze the impact of content marketing, online customer reviews, and prices on purchasing decisions for Hanasui skincare products through the TikTok application. This study uses a quantitative approach with a sample of 100 respondents. Data were analyzed using multiple regression line analysis using IBM SPSS Statistics. The study findings show that, directly, content marketing has a significant impact on purchasing decisions for Hanasui skincare products through the TikTok application, online customer reviews have a significant impact on purchasing decisions for Hanasui skincare products through the TikTok application, and prices have a significant impact on purchasing decisions for Hanasui skincare products through the TikTok application. In addition, content marketing, online customer reviews, and prices simultaneously influence purchasing decisions for skincare products.